2018
DOI: 10.1039/c8fo01044g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of honey fromMimosa quadrivalvisL. (malícia) produced by theMelipona subnitidaD. (jandaíra) stingless bee on dyslipidaemic rats

Abstract: This study assessed the effects of supplementation with honey from Mimosa quadrivalvis L. (malícia) (MH) produced by jandaíra stingless bees (Melipona subnitida D.) on the lipid metabolism, antioxidant status and some intestinal health parameters of rats with diet-induced dyslipidaemia. Rats were randomly divided into four groups: healthy control (HC), dyslipidaemic control (DC), healthy experimental (EHH) and dyslipidaemic experimental (EDH). Malícia honey (MH) was administered (1000 mL kg-1) via orogastric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
2
15
0
1
Order By: Relevance
“…The effect of honey on lipid metabolism was further confirmed by Bezerra et al [114]. In this study, honey from Mimosa quadrivalvis L. produced by the Melipona subnitida D. (jandaira) stingless bee was evaluated for its effectiveness on lipid parameters, an antioxidant status and intestinal health of dyslipidaemic rats (1 g/kg) for 35 days.…”
Section: Honey In Relieving Multiple Facets Of Atherosclerosissupporting
confidence: 54%
“…The effect of honey on lipid metabolism was further confirmed by Bezerra et al [114]. In this study, honey from Mimosa quadrivalvis L. produced by the Melipona subnitida D. (jandaira) stingless bee was evaluated for its effectiveness on lipid parameters, an antioxidant status and intestinal health of dyslipidaemic rats (1 g/kg) for 35 days.…”
Section: Honey In Relieving Multiple Facets Of Atherosclerosissupporting
confidence: 54%
“…Nevertheless, although our study did not find an increase in Lactobacillales in the Ho-C group, other authors have reported an increase in Lactobacillus spp. in dyslipidaemic rats supplemented with honey (19). The difference between these reported data may be due to the fructans content in honey or Stevia rebaudiana.…”
Section: Discussionmentioning
confidence: 68%
“…In recent years, the role of gut microbiota as responsible for the relationship between high-sucrose diet and glucose intolerance has been highlighted (36). In contrast, a study performed with dyslipidemic rats reported that supplementation with honey from Mimosa quadrivalvis L. increased glucose tolerance (19). Honey is a caloric sweetener (3.4 kcal/g) composed mainly of glucose and fructose, and it is also a source of flavonoids and phenolic acids, and its composition depends on the type of flower used by bees (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetic, butyric and propionic acids were measured with a high-performance liquid chromatography (HPLC) technique using an LC 1260 Infinity system (Agilent Technologies, St. Clara, CA, USA) coupled to a photo diode detector array (PDA) detector (G1315D; Agilent Technologies) as previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%